Simultaneous phosphate and ammonium removal from aqueous solution by a hydrated aluminum oxide modified natural zeolite - Guaya Caraguay, D. (2015)
A natural zeolite (Z-N), rich in clinoptilolite, was modified (Z-Al) by incorporation of hydrated aluminum oxide (HAlO) for the simultaneous phosphate and ammonium removal. The incorporation of surface hydroxyl groups (?Al-OH) into the zeolite structure, as active groups for phosphate removal, was characterized by acid-base titrations (pHPZC=4.50.2). The phosphate sorption increases from 0.6mg-P/g for Z-N up to 7.0mg-P/g while only a slight decrease on the ammonium sorption capacity from 33mg-N/g of Z-N to 30mg-N/g for Z-Al was observed. The HAlO modified zeolite sorption capacity for both phosphate and ammonium was slightly reduced by common ions typically present in secondary waste water effluents. Column experiments revealed higher enrichment factor for ammonium (120) than for phosphate (50) using 1M NaOH as elution solution. A reduction of zeolite phosphate capacity with regeneration cycles was observed. © 2015 Elsevier B.V.